Design and preparation of a three-dimensional interface structure Al/Mg laminated composites - Tao Wang; Feng Zhong; Xin Cao; Xu Cheng; Lin Pi; Yanhui Liu; Ming Liang; Jianfeng Li (Materials & Design, 2025)
To solve the problems of low interlayer bonding strength in Al/Mg Laminated metal composites (LMCs). This work took advantage of the fact that the three-dimensional (3D) interface structure can increase the interface contact area, hinder crack propagation, and delay interface cracking, and proposed to use spark plasma sintering (SPS) to prepare Al/Mg LMCs with 3D interface structure. The influence of the sintering temperature on the interface microstructure and mechanical properties of 2A12-Al/AZ91-Mg LMCs was systematically studied. The results indicate that 2A12-Al/AZ91-Mg LMCs with 3D interface structure similar to wave shape or gear meshing shape can be obtained by SPS integrated sintering. When the SPS integrated sintering temperature increased from 420 °C to 440 °C, a typical three-layer diffusion layer was formed at the 2A12-Al/AZ91-Mg interface. Moreover, the diffusion layer gradually transformed from a solid-phase diffusion characteristic to a solid–liquid coexistence diffusion characteristic. Meanwhile, the interface shear strength at 430 °C was the largest, which was 49.4 ± 2.67 MPa. The high interfacial shear strength benefits from the hindrance and suppression of cracks by this 3D interface structure.